2017
DOI: 10.1128/mbio.01172-17
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Active Efflux and Outer Membrane Diffusion Defines Rules of Antibiotic Permeation into Gram-Negative Bacteria

Abstract: Gram-negative bacteria are notoriously resistant to antibiotics, but the extent of the resistance varies broadly between species. We report that in significant human pathogens Acinetobacter baumannii, Pseudomonas aeruginosa, and Burkholderia spp., the differences in antibiotic resistance are largely defined by their penetration into the cell. For all tested antibiotics, the intracellular penetration was determined by a synergistic relationship between active efflux and the permeability barrier. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
240
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(244 citation statements)
references
References 64 publications
4
240
0
Order By: Relevance
“…MexAB-OprM is the only efflux pump of this bacterium whose deletion makes cells highly susceptible to antibiotics, suggesting that the expression of other pumps is too low to significantly contribute to intrinsic antibiotic resistance 27 . We previously showed that hyperporination of P. aeruginosa cells allows characterization of efflux pump functions without the contribution of the outer membrane barrier 24 . To analyze the role of efflux in P. aeruginosa physiology, we integrated the gene encoding the pore under control of an IPTG-inducible promoter onto the chromosomes of strains with progressive deletions of operons encoding the efflux pumps: PΔ4-Pore lacking mexAB-OprM, mexCD-OprJ, mexXY and mexJKL , and PΔ6-Pore, a derivative of PΔ4-Pore further lacking m exEF-oprN and triABC pumps (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MexAB-OprM is the only efflux pump of this bacterium whose deletion makes cells highly susceptible to antibiotics, suggesting that the expression of other pumps is too low to significantly contribute to intrinsic antibiotic resistance 27 . We previously showed that hyperporination of P. aeruginosa cells allows characterization of efflux pump functions without the contribution of the outer membrane barrier 24 . To analyze the role of efflux in P. aeruginosa physiology, we integrated the gene encoding the pore under control of an IPTG-inducible promoter onto the chromosomes of strains with progressive deletions of operons encoding the efflux pumps: PΔ4-Pore lacking mexAB-OprM, mexCD-OprJ, mexXY and mexJKL , and PΔ6-Pore, a derivative of PΔ4-Pore further lacking m exEF-oprN and triABC pumps (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic interactions with the low permeability barrier of the outer membrane masks the activities of efflux pumps and complicates the assessment of their kinetic properties and substrate specificities 2425 . In kinetic terms, this interaction is described by two constants: the barrier factor (B-factor) that compares maximum fluxes across the outer membrane and via efflux pumps ( B = F/V, where F is the flux across the barrier and V is the maximal efflux velocity) and the efflux constant ( K E ) that relates efficiency of efflux pumps and the diffusion rate across the membrane ( K E = V/(Km 0.5k 2 ) , where Km is a Michaelis constant and k 2 is the rate constant for drug diffusion across the outer membrane) 25 .…”
mentioning
confidence: 99%
“…The number of washes was validated by determining that additional washes had no additional effect on readout . Additionally, in the past year, there has been an effort to understand the effect of various membrane components on net accumulation in whole cells, including studying the relationship between specific molecular changes in a substrate and permeation through an isolated porin in whole cells, and studying the synergy of efflux and outer membrane influx using hyperporinated strains of Gram‐negative bacteria …”
Section: Understanding Compound Uptake In Gram‐negative Bacteria: Whomentioning
confidence: 99%
“…In this case, a suitable position on EPIs can be identified by a rational design in which charged groups are attached where they would improve the penetration into bacteria. However, compounds could also penetrate through the outer membrane of Gram‐negative bacteria by routes other than those taken by porins, such as diffusion through a lipid bilayer …”
Section: Future Perspectivesmentioning
confidence: 99%